Training and Identity in a Collaborative Program. - Major, Patricia (2003)
Keywords: dept.sed; faculty_collection; sabbatical_report

Assistive Technology in the Classroom: Enhancing the School Experiences of Students with Disabilities - Dell, Amy G.; Newton, Deborah A.; Petroff, Jerry G. (Pearson Merrill Prentice Hall, 2008)
Keywords: Educational technology; United States; United States; Students with disabilities; dept.sed; faculty_collection

Education of students with visual impairments in Kenya: Trends and issues - Kiarie, M.W. (International Journal of Special Education, 2004)
Until the nineteen hundreds, people with disabilities did not receive formal educational services in Kenya. This paper discusses available educational services for individuals with visual impairments in terms of their forms, materials provided, and educational placements. Areas of most progress are discussed along with obstacles that stand in the way of efficient services for this population. This paper contributes to the rather scarce literature on educational services for students with disabilities in developing countries.
Keywords: dept.sed; peer-reviewed; ⛔ No DOI found

Educational services for students with mental retardation in Kenya - Klarie, M.W. (International Journal of Special Education, 2006)
Research pertaining to issues on educational services for individuals with disabilities in developing countries is scarce. The purpose of this article is to two fold: first, to contribute to the already existing literature, and, secondly, and perhaps more importantly, to provide a foundation for prospective readers to better understand literature regarding educational services for students with mental retardation. This article guides the reader to understand the perspectives towards students with mental retardation, discusses the definition and causes of this condition, and discusses issues pertaining to the identification, assessment and evaluation of these students in Kenya. The core of the article contains a discussion of the various placement options available for this population along with the curriculum in operation in the various settings. Existing barriers to effectively serving this population in Kenya and in other developing countries is also discussed.
Keywords: dept.sed; peer-reviewed; ⛔ No DOI found

Book Review: The big book of humorous training games. - Saltman, JM (Humor-International Journal of Humor Research, 2005)
Keywords: book.review; dept.sed; ⛔ No DOI found

Teachers’ literacy-related knowledge and self-perceptions in relation to preparation and experience - Spear-Swerling, Louise; Brucker, Pamela Owen; Alfano, Michael P (Annals of Dyslexia, 2005)
After rating their own literacy-related knowledge in three areas (knowledge about reading/reading development, phonemic awareness/phonics, and morpheme awareness/structural analysis), graduate teacher-education students completed five tasks intended to measure their actual disciplinary knowledge in these areas. Teachers with high levels of prior background (i.e., course preparation and experience) rated themselves as significantly more knowledgeable than did low-background teachers in all areas; high-background participants also significantly outperformed low-background participants on all tasks. However, even high-background teachers scored well below ceiling on the tasks. Regression analyses indicated that teachers' self-perceptions and knowledge were positively influenced by both level of preparation and teaching experience, although the influences on teachers' knowledge differed by task. Teachers had some accurate perceptions of their own knowledge, especially in the area of phonics. Results suggest that differentiating levels of preparation may be useful in studying teacher knowledge, and also support the notion of a substantial gap between research on reading and teacher preparation in reading.
Keywords: *Faculty; *Phonetics; *Professional Competence; *Reading; *Self Concept; Adult; Certification; Child; Credentialing; Education, Graduate; Education, Special; Educational Measurement; Faculty; Female; Humans; Literacy; Male; Phonetics; Professional Competence; Professional development; Reading; Self Concept; Semantics; Teacher education; Teacher knowledge; Teacher perceptions; Teacher preparation; United States; Vocabulary; academic achievement; accreditation; adult; article; certification; child; dept.sed; education; female; human; linguistics; male; phonetics; professional competence; reading; self concept; semantics; university

Fourth graders' performance on a state-mandated assessment involving two different measures of reading comprehension - Spear-Swerling, Louise (Reading Psychology, 2004)
This study examined fourth graders' performance on two reading comprehension measures, involving a question-answering format and a cloze format, which were part of a state-mandated assessment. Word-level reading skills and oral language comprehension were important to success on both formats, but word accuracy had a stronger relationship to the cloze than to the question-answering measure. Language comprehension related strongly to both formats. The cognitive profiles associated with poor reading comprehension varied, but most often involved a specific difficulty in accuracy of pseudoword decoding. The results suggest that test format should be considered in interpreting reading comprehension performance and underscore the need to assess specific component abilities in reading.
Keywords: dept.sed

Preparing novice teachers to develop basic reading and spelling skills in children. - Spear-Swerling, Louise; Brucker, Pamela Owen (Annals of Dyslexia, 2004)
This study examined the word-structure knowledge of novice teachers and the progress of children tutored by a subgroup of the teachers. Teachers' word-structure knowledge was assessed using three tasks: graphophonemic segmentation, classification of pseudowords by syllable type, and classification of real words as phonetically regular or irregular. Tutored children were assessed on several measures of basic reading and spelling skills. Novice teachers who received word-structure instruction outperformed a comparison group of teachers in word-structure knowledge at post-test. Tutored children improved significantly from pre-test to post-test on all assessments. Teachers' post-test knowledge on the graphophonemic segmentation and irregular words tasks correlated significantly with tutored children's progress in decoding phonetically regular words; error analyses indicated links between teachers' patterns of word-structure knowledge and children's patterns of decoding progress. The study suggests that word-structure knowledge is important to effective teaching of word decoding and underscores the need to include this information in teacher preparation.
Keywords: *Dyslexia/th [Therapy]; *Education/td [Trends]; *Reading; Adult; Articulation Disorders; Articulation Disorders/rh [Rehabilitation]; Child; Dyslexia; Education; Faculty; Female; Health Knowledge, Attitudes, Practice; Humans; Male; Reading; adult; article; attitude to health; child; dept.sed; dyslexia; education; evaluation; female; human; male; reading; speech disorder; university

Teachers’ acquisition of knowledge about English word structure - Spear-Swerling, Louise; Brucker, Pamela Owen (Annals of Dyslexia, 2003)
Previous research suggests that teachers' knowledge about English word structure (e.g., the phonological structure of words and common orthographic patterns in English) may be limited, although this knowledge is important for effective teaching of word decoding. This study examined teacher education students' knowledge about word structure, and improvements in their knowledge as a result of instruction, using three tasks: graphophonemic segmentation, classification of pseudowords by syllable type, and classification of real words as phonetically regular or irregular. Participants came from a special education certification program and included both preservice and inservice teachers. Results indicated that prior preparation to teach reading influenced participants' initial performance on two of the three word-structure tasks (all but graphophonemic segmentation); however, prior experience in teaching reading did not influence word-structure knowledge. A subset of participants who received specific instruction about word structure improved their knowledge relative to a comparison group of teacher education students who did not receive word-structure instruction. Prior preparation did not influence participants' responsiveness to instruction. Conclusions support the viewpoint that teacher education must include information about English word structure for educators who will teach reading and suggest that sufficiently intensive instruction may be important in developing word-structure knowledge.
Keywords: dept.sed

What science offers teachers of reading - Spear-Swerling, Louise; Sternberg, Robert J (Learning Disabilities Research and Practice, 2001)
Keywords: dept.sed

How qualified are you and how long will you stay?: an exploratory study of novice teachers' perceptions of preparation, inducation and attrition - Mongillo, Maria (2009)
Keywords: dept.sed

A literacy tutoring experience for prospective special educators and struggling second graders. - Spear-Swerling, Louise (Journal of Learning Disabilities, 2009)
This study examined the learning of teacher candidates taking a language arts course in a special-educator preparation program and that of the second graders they tutored in a supervised field component of the course. Teacher candidates' knowledge of literacy instruction was assessed using five knowledge tasks; children were assessed on several measures of basic reading and spelling skills as well as on their knowledge of phonics concepts such as syllable types. Teacher candidates generally had inaccurate perceptions of their knowledge at pretest, but their knowledge improved significantly on all tasks after course instruction. Tutored children improved significantly from pre- to posttest on all assessments. The study suggests that carefully designed literacy coursework with field experiences can benefit both prospective special educators and struggling readers.
Keywords: *Education, Professional/st [Standards]; *Education, Special/st [Standards]; *Educational Status; *Professional Competence/st [Standards]; *Reading; *Remedial Teaching/st [Standards]; Adolescent; Adult; Child; Culture; Curriculum; Curriculum/st [Standards]; Education, Professional; Education, Special; Educational Status; Female; Humans; Linguistics; Linguistics/ed [Education]; Male; Middle Aged; Phonetics; Professional Competence; Questionnaires; Reading; Remedial Teaching; Self Concept; Special education; Surveys and Questionnaires; Teacher education; Teacher knowledge; Teacher perceptions; Young Adult; adolescent; adult; article; child; cultural anthropology; curriculum; dept.sed; education; educational status; female; human; linguistics; male; middle aged; phonetics; professional competence; questionnaire; reading; self concept; standard; teaching; vocational education

Assistive technology - Newton, Deborah A.; Dell, Amy G. (Journal of Special Education Technology, 2009)
Keywords: dept.sed

Assistive technology - Newton, Deborah A.; Dell, Amy G. (Journal of Special Education Technology, 2009)
Keywords: dept.sed

Assistive technology - Newton, Deborah A.; Dell, Amy G. (Journal of Special Education Technology, 2009)
Keywords: dept.sed

Comparing teachers' literacy-related knowledge to their state's standards for reading - McCombes-Tolis, Jule; Feinn, Richard (Reading Psychology, 2008)
This study compared elementary and special education teachers' knowledge of when K-3 students develop key reading competencies, their knowledge of who is responsible for teaching K-3 students key reading competencies, and teachers' perceptions of their own instructionally relevant competencies to those standards articulated within their state's blueprint for reading achievement. Results reveal a disconnect between teacher-held beliefs and state-articulated grade-level student literacy competencies. Results also suggest that teacher preparation programs are not preparing candidates to achieve mastery of essential teacher competencies articulated within their state's reading blueprint. Strengthening the accountability of teacher preparation practices to states' reading blueprint standards is recommended. Copyright © Taylor & Francis Group, LLC.
Keywords: dept.sed

School-wide intervention in the childhood bullying triangle - Mcnamee, Abigail; Mercurio, Mia (Childhood education, 2008)
Keywords: dept.sed

Effective Social Interaction Strategies for Inclusive Settings. - Terpstra, Judith; Tamura, Ronald (Early Childhood Education Journal, 2008)
Many strategies and interventions exist in the education of young children with disabilities. One area of intervention is that of social interaction, including social skills instruction, peer interaction strategies, and play skills. Interaction and social skill strategies for use with children with and without disabilities for the purpose of increasing social interactions between children with and without disabilities in educational settings is an area many educators of early childhood special education strive to find in an effective and easy to implement format. Several strategies from research are presented in this article. Only strategies that were demonstrated to be successful through reported research are discussed. Strategies are identified according to their ease of implementation and effectiveness., (C)2008 Kluwer Academic Publishers
Keywords: Peer interaction; Play skills; Play strategies; Social interaction; Social skills; Social strategies; dept.sed

Children's reading comprehension and oral reading fluency in easy text - Spear-Swerling, Louise (Reading and Writing, 2006)
This study explored third-graders' oral reading fluency (ORF) in easy text in relation to their third- and fourth-grade reading comprehension. It also examined the children's performance on two different measures of text exposure, a self-report questionnaire and a title-recognition test. Although third-graders' ORF related significantly to their reading comprehension, oral language comprehension accounted for most of the variance in reading comprehension, whereas single word reading speed accounted for most of the variance in ORE Third-grade reading comprehension and ORF each predicted unique variance in children's scores on a fourth-grade state-mandated reading comprehension assessment. Scores on the self-report questionnaire correlated significantly with third-grade ORF and fourth-grade reading; the self-report accounted for reliable variance in ORF even with all of the other reading ability variables entered first. Results are consistent with the viewpoint that text exposure affects reading fluency. They also demonstrate that ORF is a valuable predictor of middle-elementary children's reading comprehension, even when the ORF measure employs very easy text in which children achieve near-perfect word accuracy.
Keywords: Comprehension; Fluency; Reading; Text exposure; dept.sed; peer-reviewed

The research-practice divide in beginning reading - Spear-Swerling, Louise (Theory into Practice, 2007)
An extensive research base on beginning reading acquisition and reading difficulties, developed over the past few decades, has important implications for the teaching of reading. Unfortunately, much of this research does not appear to be reaching teachers, whose knowledge is essential for scientific findings about reading to benefit children. This article focuses on two key areas of teachers' research-based disciplinary knowledge for teaching reading: knowledge about children's early reading development and knowledge about English word structure. Evidence demonstrating a gap between teacher knowledge in these areas and current scientific findings is reviewed. Next, possible reasons for the gap are explored. The article concludes with suggestions for educators who are interested in acquiring additional research-based knowledge about reading.
Keywords: dept.rdg; dept.sed